Cloud Computing Analysis of Hybrid Networks on Raspberry - Liza, Risko; Fitriana, Liza; Junaidi, Junaidi; Siddiq, Daffa Maulana (Politeknik Ganesha Medan, 2023)
There are already a lot of cloud services on the internet which provide services, some of them even provide free facilities, but they are still limited in usage and capacity. Capacity is calculated based on saved files, temporary files, and even trash files. Moreover, data security cannot be guaranteed because the hardware is not properly set or owned by someone else. The cloud used cannot guarantee the connection and the bandwidth. The stigma of building cloud computing revolves around huge costs, not limited to operational and maintenance costs, nor the proper location for the cloud network equipment. As an effort to build data storage with large capacity, bandwidth regulation, and data protection, which is located in a private location, building a cloud computing service system which is efficient in time, cost, and place, and has good performance is no longer an impossible thing to do. With the help of Microcontroller technology, Raspberry Pi, a Cloud Computing with a Hybrid network could be built to reduce cost, time and space for the system. With the NextCloud application embedded into the cloud computing server, performance can be improved, including easy data synchronization that will flawlessly operate as a Client Server on a wide variety of today’s devices with examples being PCs, Tablets, Notebooks or Smartphones.